DD-08 RETAINER II – DEVELOPMENT AND VALIDATION OF A PATIENT REPORTED OUTCOME MEASURE (PROM) FOR INGUINAL HERNIA REPAIR. (13th October 2022) - Corghan, S; Fullard, A; Fleming, C; ,
Abstract: Aim: Outcome reporting following inguinal hernia repair is heterogenous. We aim to develop an inguinal hernia repair PROM. Methods: The evaluation and development of a disease-specific instrument will be performed in accordance with FDA guidelines for developing PROMs in three phases Item generation Pre-testing PROM evaluation Item Generation: An systematic review(PROSPERO ID CRD42021271735) and narrative analysis will be undertaken to identify health related quality of life(HrQoL) issues relevant to patients with inguinal hernia, this will be used to identify themes and concepts to help inform the interview guide. Pre-Testing: A pre-test questionnaire will be developed based on the conceptual framework devised in Phase I and tested with a sample of 20–30 patients to reach consensus regarding the questionnaire format and structure to confirm that instructions and items are clear, understandable, relevant, and applicable. Quantitative assessment of face validity of the measure will be undertaken using the QQ-10 and data fanalysed both quantitatively and qualitatively. PROM Evaluation: A field test will be undertaken to evaluate the RETAINER II tool for reliability and validity using psychometric techniques from Classical Test Theory. Each patient will complete: RETAINER II tool HERQL Carolina Comfort Scale EuraHS-QoL An approximate sample of 50–100 patients will be purposively sampled ensuring representation of all subgroups. Qualitative analysis, using NVIVO 12 for Windows(QSR International Pty Ltd., Australia) will be performed independently. A test-retest will be undertaken. Consenting participants will complete a second questionnaire pack 5–7 days after inital questionnaires (approximately 50 patients).